Understanding and controlling the microstructure of complex foods - McClements, David Julian (CRC Press ; Woodhead Pub., 2007)
Annotation With its distinguished editor and array of international contributors, this book provides a review of current understanding of significant aspects of food structure and methods for its control. It begins with coverage of the fundamental structural elements present in foods and the forces which hold them together, discusses novel analytical techniques which can provide information on the morphology and behaviour of food materials, then examines how the principles of structural design can be employed to improve performance and functionality of foods. The book concludes with a discussion of how this knowledge can be implemented to improve properties of foods.
Keywords: Food -- Composition.; Food -- Analysis.; Food industry and trade.; elektronické knihy; electronic books